Speculations - Ennis, Paul J. (punctum books, 2020)
From the Editorial Introduction: "Since I am convinced that nobody reads editorials I will keep my remarks brief. Putting together the inaugural issue of Speculations has been an unusual experience. It has depended on the collusion of fellow speculative types, the help of many anonymous reviewers, the endless patience of designer Thomas Gokey, and more hours than someone in the final year of their PhD should ever spend on a project. Looking over the final product I think it has all been worth it. This is the first journal dedicated to speculative realism and despite the obscurity of that term I think we all understand it as a handy label under which weird realists, continental metaphysicians, object oriented ontologists, transcendental realists, vitalists, and Lovecraftians can unite. This is also, perhaps, the first time a journal can boast that each contributor is also a blogger. This is the reason why Speculations could only ever be an online, open-access journal. ..."